2020
DOI: 10.3389/fcell.2020.00822
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Targets SIRT3 to Enhance SOD2 Activity in Mitochondria

Abstract: Caffeine is chemically stable and not readily oxidized under normal physiological conditions but also has antioxidant effects, although the underlying molecular mechanism is not well understood. Superoxide dismutase (SOD) 2 is a manganesecontaining enzyme located in mitochondria that protects cells against oxidative stress by scavenging reactive oxygen species (ROS). SOD2 activity is inhibited through acetylation under conditions of stress such as exposure to ultraviolet (UV) radiation. Sirtuin 3 (SIRT3) is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…Caffeine can also mechanistically facilitate the elimination of ROS by activating autophagy through the inhibition of AR, increasing the level of sirtuin 3 (SIRT3) and the activation of 5′ adenosine monophosphate-activated protein kinase [ 199 ]. Similar investigations were also conducted by Xu et al [ 200 ], and the authors showed that caffeine (4–512 μM) promoted SIRT3 activity and reduced SOD2 (superoxide dismutase 2) acetylation. The results of the above studies show that caffeine targets SIRT3 to enhance SOD2 activity and protect skin cells from UV irradiation-induced oxidative stress.…”
Section: Caffeine and Oxidative Stresssupporting
confidence: 80%
See 1 more Smart Citation
“…Caffeine can also mechanistically facilitate the elimination of ROS by activating autophagy through the inhibition of AR, increasing the level of sirtuin 3 (SIRT3) and the activation of 5′ adenosine monophosphate-activated protein kinase [ 199 ]. Similar investigations were also conducted by Xu et al [ 200 ], and the authors showed that caffeine (4–512 μM) promoted SIRT3 activity and reduced SOD2 (superoxide dismutase 2) acetylation. The results of the above studies show that caffeine targets SIRT3 to enhance SOD2 activity and protect skin cells from UV irradiation-induced oxidative stress.…”
Section: Caffeine and Oxidative Stresssupporting
confidence: 80%
“…The results of the above studies show that caffeine targets SIRT3 to enhance SOD2 activity and protect skin cells from UV irradiation-induced oxidative stress. Thus caffeine, as a small-molecule SIRT3 activator, could be a potential agent to protect human skin against UV radiation [ 200 ].…”
Section: Caffeine and Oxidative Stressmentioning
confidence: 99%
“…Furthermore, previous studies showed that the upregulation of SIRT3-mediated SOD2 and PRDX3 deacetylation could enhance the mitochondrial antioxidant defense activity and alleviate oxidative damage to the mitochondria [ 71 , 72 ]. Moreover, SIRT3 can promote SOD2 transcription by interacting with the FOXO3 α proteins and activating the FOXO3 α -dependent antioxidant-encoding gene SOD2 [ 73 ]. A similar regulation has been reported between SIRT1 and PRDX3 [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of ROS in HaCaT cells will promote the release of cytochrome C to the cytoplasm, activate the caspase cascade and cause cell apoptosis [ 24 ]. The results showed that UV-B irradiation significantly increased the activation of caspase 3 and caspase 9 and the expression of Bax in the model group, while the antiapoptotic protein Bcl-2 decreased significantly.…”
Section: Resultsmentioning
confidence: 99%